Dynamic Output Feedback Stabilization of Controlled Positive Discrete-Time Systems with Delays. (18th October 2010) - Li, Zhenbo; Zhu, Shuqian
Abstract : The problem of stabilization by means of dynamic output feedback is studied for discrete-time delayed systems with possible interval uncertainties. The control is under positivity constraint, which means that the resultant closed-loop system must be stable and positive. The robust resilient controller is respect to additive controller gain variation which also belongs to an interval. Necessary and sufficient/sufficient conditions are established for the existence of the dynamic output feedback controller. The desired controller gain matrices can be determined effectively via the cone complementarity linearization techniques.